AI can help but also harm. - Csortea, Krisztina (World Today)
The article addresses ethical issues raised when applying artificial intelligence (AI) to humanitarian crises. Topics discussed include estimated number of forcibly displaced people in the world by the end of 2021 as a result of persecution, conflict, violence and human rights violations, according to the United Nations (UN) High Commission for Refugees, increased benefits promises by AI for humanitarians, and data hack suffered by the International Committee of the Red Cross.